LEKSIKON ETNOMEDISIN PENGOBATAN TRADISIONAL PADA MASYARAKAT MELAYU DESA PUNGGUR KAPUAS KABUPATEN KUBU RAYA - Lavianasari, Rita; Wartiningsih, Agus; Syahrani, Agus (Universitas Tanjungpura, 2023)
This study aims to describe and analyze the ethnomedicine lexicon of traditional medicine in the Malay community of Punggur Kapuas village, Kubu Raya district. This research was using descriptive method with the form of qualitative research. Sources of data in this study directly from the informant. The data obtained in this study resulted in 80 ethnomedicinal lexicon of traditional medicine in the Malay community of Punggur Kapuas village, Kubu Raya district, namely based on the name of the disease, totaling 31 lexicon consisting of 21 lexicon of disease names in Sambas Malay and 10 lexicon of disease names in Pontianak Malay, treatment materials. totaling 49 lexicon consisting of 30 lexicon names of medicinal ingredients in Malay Sambas and 19 lexicon names of ingredients in Pontianak Malay language. The form of the ethnomedicinal lexicon of traditional medicine in the Malay community of Punggur Kapuas village, Kubu Raya district is in the form of 40 lexicon monomorphemics and 40 lexicon phrases. The meaning of the ethnomedicine lexicon of traditional medicine in the Malay community of Punggur Kapuas village, Kubu Raya district based on 80 lexical meanings and 6 lexical meanings of cultural meaning. The form of Indonesian language learning text based on the ethnomedicine lexicon of traditional medicine in the Malay community of Punggur Kapuas village, Kubu Raya district is a descriptive text.